Hot-wire chemical vapor deposition low-loss hydrogenated amorphous silicon waveguides for silicon photonic devices - Oo, Swe Z. (2021)
We demonstrate low-loss hydrogenated amorphous silicon (a-Si:H) waveguides by hot-wire chemical vapor deposition (HWCVD). The effect of hydrogenation in a-Si at different deposition temperatures has been investigated and analyzed by Raman spectroscopy. We obtained an optical quality a-Si:H waveguide deposited at 230°C that has a strong Raman peak shift at 480 cm , peak width (full width at half-maximum) of 68.9 cm , and bond angle deviation of 8.98°. Optical transmission measurement shows a low propagation loss of 0.8 dB/cm at the 1550 nm wavelength, which is the first, to our knowledge, report for a HWCVD a-Si:H waveguide.